NCAA Drug Testing: Finding a Constitutional Balance - Judge, William J. (My University, 1986)
This was reprinted, with permission, from the Spring 1986 issue of the Sports Lawyers Newsletter. The paper reviewed court cases about drug testing of students and whether or not the NCAA had a right to drug test athletes under the purview of the U.S. Constitution and based on legal precedents.
Keywords: drugs/alcohol; legal issues